Hidrólise ácida da farinha da casca de pequi (Caryocar brasiliense) visando à produção de bioetanol - Silva, Diana Lopes da (Universidade Federal do Tocantins, 2020)
With the increase in world population and the number of countries that became industrialized , energy consumption has increased too. With this continued growth in demand for energy, there is a clear trend of resource depletion , as the main source for the production of fossil fuels are non-renewable . In this context, the search for renewable energy and alternatives to petroleum is mobilizing the academic , industrial , governmental and social . In the short term , biomass presents itself as the only appropriate use of renewable energy source that can provide alternative fuels , such as second-generation ethanol . The Cerrado presents various raw materials that can be used for this purpose . Pequi ( Caryocar brasiliense ) , is a typical fruit of the Brazilian cerrado that blooms between June and September and produces fruit from September to February . The peel Pequi is made by exocarp and outer mesocarp by a thicker layer and fleshy and has a high carbohydrate content. It is considered a waste , because it is not utilized for human consumption . Due to these characteristics , the use of peel becomes Pequi an alternative to energy production. Thus, this study aimed to acid hydrolysis flour peell Pequi . To obtain the flour peel Pequi were used fruits from the city of Palmas -TO and its physicochemical characterization performed . For hydrolysis with dilute acid were studied variables of time ( 30,45,60 , and 90 min ) and concentration of sulfuric acid (1, 2, 3, 4 and 5%v/v) at four temperatures (106°C , 111°C , 116°C and 121°C) with tress replicates. Among the treatments tested, which showed the best results was performed at 121ºC and a sulfuric acid concentration of 5% v/v hydrolysis time of 90 min to yield a concentration of 7,34 mg / ml sugar reducing (AR) , representing an increase of almost 9 times of AR in relation to the initial content contained in the peel flour pequi .